Code-switching practices among the multilingual community college students in Sabah / Johan @ Severinus Tati - Tati, Johan @ Severinus (2022)
The phenomenon of combining and shifting between languages among multilingual ESL learners in the second language classroom has become one of the main concerns of sociolinguistics in the multilingual classroom. The situation happens in most multilingual classrooms, including ESL classrooms in Sabah. Although much research has been done on code-switching in ESL classrooms, there is inadequate research on the code-switching practises among the multilingual community college students in Sabah. Thus, this study aims to address this gap. It aims to investigate the event of code- switching in classroom interaction among community college students in Sabah. The quantitative data were obtained by distributing a questionnaire to 125 students in semester one from a community college in Sabah. The classroom observation and semi- structured interviews were conducted to obtain qualitative data. Quantitative data were analysed using the statistical software SPSS 24.0 and presented in frequency and percentages. Qualitative data were analysed using Atlas. ti. The findings revealed that the Sabah Malay dialect (SMD) was the domain language used in interactions with classmates and instructors. The students also responded positively to using code- switching to facilitate their English learning pace. These findings implicated that code- switching was a functional language tool for interaction among the multilingual community college students in Sabah.